Multiple-Hit Hypothesis in Parkinson’s Disease: LRRK2 and Inflammation - Cabezudo, Diego (Front Neurosci, 2020)
The multiple hit hypothesis for Parkinson’s disease (PD) suggests that an interaction between multiple (genetic and/or environmental) risk factors is needed to trigger the pathology. Leucine-Rich Repeat Kinase 2 (LRRK2) is an interesting protein to study in this context and is the focus of this review. More than 15 years of intensive research have identified several cellular pathways in which LRRK2 is involved, yet its exact physiological role or contribution to PD is not completely understood. Pathogenic mutations in LRRK2 are the most common genetic cause of PD but most likely require additional triggers to develop PD, as suggested by the reduced penetrance of the LRRK2 G2019S mutation. LRRK2 expression is high in immune cells such as monocytes, neutrophils, or dendritic cells, compared to neurons or glial cells and evidence for a role of LRRK2 in the immune system is emerging. This has led to the hypothesis that an inflammatory trigger is needed for pathogenic LRRK2 mutations to induce a PD phenotype. In this review, we will discuss the link between LRRK2 and inflammation and how this could play an active role in PD etiology.